A METRICS BASED APPROACH TO ANALYSE WEB USAGE PATTERN - Singh, Sukhjinder; Makkar, Amit; Singh, Navneet (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2011)
Web metrics are established goals and standards for measuring website performance. Web Analytics can be used to analyze and statistically process user and customer behavior. Web Analytics especially refers to the use of data collected from a Website to determine which aspects of the Website work towards the business objectives. This paper provides a web metrics based approach that can be used to analyze and improve web usage pattern. We define a set of 15 web metrics that can play an important role in understanding web visitors behavior and provide suggestion how these metrics can help in making a website more popular. We describe the approach by considering a case study of the website gndu.ac.in for the data collected over a period of five months.